Renewable filter screen for catalytic degradation of formaldehyde at room temperature and regeneration method thereof

By depositing nano MnOx particles on the surface of nickel foam and using electrochemical treatment, the problems of easy agglomeration, reduced activity and difficult to recover by manganese oxide catalysts are solved, and the reuse of efficient catalytic degradation of formaldehyde and catalysts are achieved.

CN119701630APending Publication Date: 2025-03-28SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411890074.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When existing manganese oxide catalysts catalyze formaldehyde degradation at room temperature under light conditions, they are prone to agglomeration, reduce catalyst activity, are difficult to recover, and there is a risk of secondary pollution.

Method used

By depositing nano MnOx particles on the surface of the foam nickel, forming a MnOx layer, and using electrochemical treatment to improve the catalytic performance, the solid-loading and reuse of the catalyst are achieved.

Benefits of technology

The efficient adsorption and catalytic degradation of formaldehyde are achieved, and the performance of the catalyst is maintained at a high level, secondary pollution is avoided, and it can be regenerated through simple methods to achieve reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701630A_ABST
    Figure CN119701630A_ABST
Patent Text Reader

Abstract

The invention relates to a reproducible filter screen for catalytic degradation of formaldehyde at room temperature and a regeneration method thereof, the reproducible filter screen for catalytic degradation of formaldehyde at room temperature is obtained by loading a MnOx layer formed by dense accumulation of nanometer MnOx particles on the surface of foamed nickel, the nanometer MnOx particles are uniform in particle size and are uniformly distributed on the surface of the foamed nickel, and the particle size of the nanometer MnOx particles is smaller than 50nm. The renewable filter screen for catalytic degradation of formaldehyde at room temperature provided by the invention has good formaldehyde adsorbability and high catalytic activity, and can quickly degrade formaldehyde in air.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts containing manganese or manganese oxide or hydroxide, and specifically relates to a regenerable room temperature catalytic degradation formaldehyde filter and a regeneration method thereof. Background Art

[0002] With the continuous development of society, people have higher and higher requirements for indoor air quality. Formaldehyde (HCHO) is one of the most common indoor air pollutants. Long-term exposure to indoor air containing HCHO can cause respiratory diseases, ranging from dizziness and nausea to nasopharyngeal cancer and leukemia. Considering the toxicity and harm of HCHO, the International Agency for Research on Cancer recommends that HCHO be listed as a human carcinogen, and the World Health Organization has proposed and stipulated that the upper limit of indoor HCHO concentration should not exceed 0.1mg / m 3 (about 0.08ppm). However, in many cases, the indoor HCHO concentration of newly renovated houses is far more than 0.08ppm. Therefore, it is of great significance to develop effective methods to absorb or degrade low-concentration HCHO indoors.

[0003] Adsorption is one of the simplest methods to remove indoor formaldehyde, but its development and application are restricted by its limited adsorption capacity and secondary pollution caused by desorption during the regeneration process. In previous studies, photocatalytic oxidation was generally used to effectively degrade indoor formaldehyde under the supplement of additional light. However, the toxic byproducts that may be produced in this process and the need for additional light sources limit its practical application.

[0004] Compared with existing photocatalysts, manganese oxide catalysts can catalytically degrade formaldehyde at room temperature without light, and have the characteristics of low cost, high efficiency, and no secondary pollution. They have great application potential in the field of catalytic oxidation of formaldehyde at room temperature. However, powdered manganese oxide catalysts are prone to agglomeration when used directly, which reduces the activity of the catalyst and is difficult to recycle. Exposure to the environment directly threatens human health.

[0005] Therefore, how to immobilize the manganese oxide catalyst and make it reusable is the key to its large-scale application. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a regenerable room temperature catalytic degradation formaldehyde filter and a regeneration method thereof in view of the deficiencies in the prior art. The room temperature catalytic degradation formaldehyde filter is obtained by loading manganese oxide on the surface of nickel foam, and after the performance declines during the test, its catalytic performance can be restored in a relatively simple manner to achieve repeated use.

[0007] One of the purposes of the present invention is to provide a regenerable room temperature catalytic degradation formaldehyde filter.

[0008] In order to achieve the above-mentioned invention object, the specific technical scheme is as follows:

[0009] A regenerable room temperature catalytic degradation formaldehyde filter, the regenerable room temperature catalytic degradation formaldehyde filter is composed of a layer of nano MnO2 loaded on the surface of nickel foam x The MnO particles are densely packed x The nano-MnO x The particle size is uniform and evenly distributed on the surface of nickel foam. x The particle size is less than 50nm.

[0010] According to the above scheme, the pore size range of the nickel foam is 75-110 PPI (pores per inch).

[0011] According to the above scheme, the regenerable room temperature catalytic degradation of MnO on the formaldehyde filter x The loading rate is 5-10wt%.

[0012] The second object of the present invention is to provide a method for preparing the above-mentioned renewable room temperature catalytic degradation formaldehyde filter.

[0013] In order to achieve the above-mentioned invention object, the specific technical scheme is as follows:

[0014] A method for preparing a renewable room temperature catalytic degradation formaldehyde filter, the specific steps are as follows:

[0015] S1: prepare sodium thiosulfate aqueous solution and potassium manganate aqueous solution respectively;

[0016] S2: After cleaning the nickel foam, place it in the sodium thiosulfate aqueous solution and potassium permanganate aqueous solution obtained in step S1 in turn to soak, and generate MnO on the surface of the nickel foam. x , and then dried to obtain MnO x / NF filter;

[0017] S3: Using a three-electrode method, potassium hydroxide solution is used as the electrolyte, and the MnO obtained in step S2 is used x / NF filter is used as anode (working electrode), stone mill rod is used as cathode, Ag / AgCl is used as reference electrode, electrochemical reaction is carried out, and finally drying is performed to obtain a renewable room temperature catalytic degradation formaldehyde filter.

[0018] According to the above scheme, the concentration of the potassium permanganate aqueous solution in step S1 is 3-5 g / L, and the concentration of the sodium thiosulfate aqueous solution is 10-15 g / L.

[0019] According to the above scheme, the method for cleaning the nickel foam in step S2 is: placing the nickel foam in a hydrochloric acid solution (0.8-1.2 mol / L), deionized water, and anhydrous ethanol in sequence and ultrasonically shaking for 10-60 min.

[0020] According to the above scheme, step S2 generates MnO on the surface of nickel foam. x The method is as follows: the cleaned nickel foam is first immersed in a sodium thiosulfate aqueous solution for 5-10 minutes, and then immersed in a potassium permanganate aqueous solution for 5-10 minutes, which is regarded as one process, and the process is repeated 5-10 times.

[0021] According to the above scheme, the drying temperature in step S2 is 50-100°C and the drying time is 6-24h.

[0022] According to the above scheme, the concentration of the potassium hydroxide solution in step S3 is 0.5-1.2 mol / L.

[0023] According to the above scheme, the electrochemical reaction conditions of step S3 are: reaction voltage is 0.1-0.7V, and reaction time is 0.5-3.5h.

[0024] According to the above scheme, the drying temperature of S3 is 50-100°C and the drying time is 6-24h.

[0025] The third object of the present invention is to provide an air purifier prepared according to the above-mentioned renewable room temperature catalytic degradation formaldehyde filter.

[0026] A fourth object of the present invention is to provide a method for regenerating the above-mentioned regenerable room temperature catalytic degradation formaldehyde filter.

[0027] In order to achieve the above-mentioned invention object, the specific technical scheme is as follows:

[0028] A regeneration method for a renewable room temperature catalytic degradation formaldehyde filter, the specific steps are as follows: adopting a three-electrode method, using potassium hydroxide solution as an electrolyte, using a used room temperature catalytic degradation formaldehyde filter as an anode (working electrode), a stone mill rod as a cathode, and Ag / AgCl as a reference electrode, performing an electrochemical reaction, and finally performing a heat treatment to obtain a renewable room temperature catalytic degradation formaldehyde filter.

[0029] According to the above scheme, the concentration of the potassium hydroxide solution is 0.5-1.2 mol / L.

[0030] According to the above scheme, the electrochemical reaction conditions are: reaction voltage is 0.1-0.7V, and reaction time is 0.5-3.5hmin.

[0031] According to the above scheme, the heat treatment temperature is 50-100°C and the heat treatment time is 6-24h.

[0032] The principle of the present invention is as follows:

[0033] The present invention firstly uses a chemical deposition method to deposit a layer of MnO with high catalytic activity on the surface of nickel foam with high specific surface area. x, so that the catalyst is dispersed and distributed, exposing more active sites, and immobilized on the surface of highly conductive nickel foam, and then electrochemical treatment is used to further improve the catalytic performance of the filter. On the one hand, electrochemical treatment makes the surface of nickel foam nano-MnO x The particle distribution is more uniform, which is conducive to the adsorption of formaldehyde. In addition, the electrochemical treatment makes MnO x The oxidation state and surface active oxygen content of the catalyst change, which can accelerate the catalytic reaction.

[0034] During use, filters based on catalytic oxidation face the problem of continuously declining catalytic performance. The regeneration method provided by the present invention can maintain the high catalytic performance of the filter. The method adopted is to first restore the active oxygen content on the catalyst surface by an electrochemical method, and then remove the intermediates accumulated on the catalyst surface by heat treatment, so that the catalyst active sites are exposed again. The increase in the active oxygen content on the catalyst surface helps to quickly catalytically degrade and remove intermediates during the heat treatment stage. Therefore, the present invention can maintain the performance of the catalyst at a high level by combining electrochemical treatment and heat treatment, and provides a new method for the reuse of catalysts.

[0035] The beneficial effects of the present invention are: 1. The regenerable room temperature catalytic formaldehyde degradation filter provided by the present invention has good formaldehyde adsorption, high catalytic activity, and can quickly degrade formaldehyde in the air; 2. The regeneration method of the present invention uses electrochemistry combined with heat treatment to regenerate the filter whose catalytic performance has decreased after use, which can restore the oxidation state and active oxygen content of the catalyst, remove intermediates accumulated during use, and improve the catalytic degradation activity of formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The Raman spectra of the MnOx / NF filter prepared in Example 1 of the present invention before and after pretreatment and the nickel foam;

[0037] Figure 2 This is a scanning electron microscope image of the clean nickel foam obtained in step S2 of Example 1;

[0038] Figure 3 MnO obtained in step S2 of Example 1 x / SEM image of NF filter;

[0039] Figure 4 This is a scanning electron microscope image of the regenerable room temperature catalytic degradation formaldehyde filter obtained in step S3 of Example 1;

[0040] Figure 5 The XPS spectra of Mn 2p before and after electrochemical pretreatment of the MnOx / NF filter in step S3 of Example 1;

[0041] Figure 6XPS spectra of O1S before and after electrochemical pretreatment of MnOx / NF filter in step S3 of Example 1;

[0042] Figure 7 This is a static test performance comparison diagram of the MnOx / NF filter before and after electrochemical pretreatment in step S3 of Example 1;

[0043] Figure 8 This is a comparison chart of the half-hour degradation rate of the first static test of the MnOx / NF filter and the static test after four regeneration treatments in Example 2;

[0044] Fig. 9 This is a comparison chart of the half-hour degradation rate of the first static test of the MnOx / NF filter in Example 2 and the static test after four room temperature static treatments;

[0045] Fig.10 This is a comparison chart of the half-hour degradation rate of the MnOx / NF filter screen in Example 2 in the first static test, the static test after four room temperature static treatments, and the static test after regeneration treatment;

[0046] Fig.11 This is a comparison chart of the half-hour degradation rate of the first static test and the static test after four heat treatments of the MnOx / NF filter in Example 2;

[0047] Fig.12 Example 2MnO x / XPS spectra of Mn 2p of NF filter before static test, after five static tests and after one regeneration treatment;

[0048] Fig.13 Example 2MnO x / XPS spectra of O1S of NF filter before static test, after five static tests and after one regeneration treatment;

[0049] Fig.14 Example 2MnO x XPS spectra of C1S of the NF filter before static testing, after five static tests, and after one regeneration treatment. DETAILED DESCRIPTION

[0050] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below using embodiments in conjunction with the accompanying drawings.

[0051] Example 1

[0052] A renewable room temperature catalytic degradation formaldehyde filter, the preparation method of which comprises the following steps:

[0053] S1: Dissolve 5 g of sodium thiosulfate and 2 g of potassium permanganate in 400 mL of deionized water to prepare a sodium thiosulfate aqueous solution (12.5 g / L) and a potassium permanganate aqueous solution (5 g / L), respectively;

[0054] S2: The nickel foam (8.5 cm × 6.5 cm × 0.1 cm, 110 PPI) was subjected to ultrasonic oscillation treatment in 1 mol / L hydrochloric acid solution, deionized water and anhydrous ethanol for 20 min to obtain a clean nickel foam. The clean nickel foam was first immersed in the sodium thiosulfate aqueous solution prepared in S1 for 10 min, and then immersed in the potassium permanganate aqueous solution prepared in S1 for 10 min. This was regarded as one process, and the process was repeated 6 times to uniformly load MnOx on the nickel foam.

[0055] The filter was placed in an oven at 75°C and dried for 24 h to obtain a MnOx / NF filter;

[0056] S3: The MnOx / NF filter was electrochemically pretreated: The MnOx / NF filter obtained in S2 was used as the anode, the stone mill rod as the cathode, Ag / AgCl as the reference electrode, and potassium hydroxide solution (1 mol / L) as the electrolyte to build a three-electrode system for electrochemical reaction. The voltage was set to 0.5 V on the electrochemical workstation, and the treatment time was 60 min. After the reaction was completed, it was placed in a 70 ° C oven and dried for 24 h to obtain a renewable room temperature catalytic degradation formaldehyde filter (MnO x The loading rate was 6.25 wt%).

[0057] The Raman spectra of the MnOx / NF filter screen prepared in this embodiment before and after pretreatment and the nickel foam are shown in FIG. Figure 1 As shown in the figure, compared with the unloaded nickel foam, the Raman spectra of the MnOx / NF filter before and after pretreatment are both at 600 cm -1 There is obvious MnO x The characteristic peaks of MnO2 in step S2 are shown in Figure 2, indicating that MnO2 was successfully deposited by chemical deposition in step S2. x Loaded on nickel foam, MnO x Still retained.

[0058] Figure 2 This is a scanning electron microscope image of the clean nickel foam obtained in step S2 of this embodiment, showing that its surface is relatively smooth without obvious particles.

[0059] Figure 3 The MnO obtained in step S2 of this embodiment x The scanning electron microscope image of the NF filter shows that a large number of MnO particles with a diameter of less than 50 nm are densely grown on the surface of the nickel foam. x The disordered stacking of particles and nanoparticles makes MnO x / NF surface is uneven.

[0060] Figure 4 This is a scanning electron microscope image of the regenerable room temperature catalytic degradation formaldehyde filter obtained in step S3 of this embodiment. It can be seen that after the electrochemical pretreatment, the nanoparticles on its surface are more evenly distributed.

[0061] Figure 5 This is the XPS spectrum of Mn 2p before and after electrochemical pretreatment of the MnOx / NF filter in step S3 of this embodiment. It can be seen that after electrochemical pretreatment, the surface Mn 4+ The content increased from 35.64% to 45.15%, Mn 3+ The content increased from 31.20% to 54.85%, Mn 2+ The content dropped from 33.16% to 0%, indicating that the electrochemical pretreatment increased the oxidation state of the catalyst surface and promoted the degradation of formaldehyde at room temperature.

[0062] Figure 6 This is the XPS spectrum of O1S before and after electrochemical pretreatment of the MnOx / NF filter in step S3 of this embodiment. It can be seen that after electrochemical pretreatment, the surface adsorbed oxygen (O ads ) content increased from 46.27% to 50.58%, and the surface lattice oxygen (O latt ) content increased from 14.54% to 19.36%. Surface adsorbed oxygen and surface lattice oxygen are important active oxygen species for the catalytic degradation of formaldehyde at room temperature. The increase of their content can improve the catalyst activity.

[0063] Figure 7 This is a static test performance comparison chart of the MnOx / NF filter before and after the electrochemical pretreatment in step S3 of this embodiment. The specific test method is as follows: the filter is first sealed with plastic wrap and placed in a 216L glass box, the glass box is sealed with vacuum silicone, a hose with 1mL formaldehyde solution (36-38%) is placed in the small hole above the glass box, and the volatile formaldehyde is evenly dispersed by a fan placed in the glass box. A fixed formaldehyde detector is used to detect the formaldehyde concentration in the glass box in real time. After the formaldehyde concentration is controlled to be stable at about 1ppm, the hose with the formaldehyde solution is taken out, and the plastic wrap covering the surface of the filter is opened to start testing the formaldehyde concentration in the glass box. The test results show that the MnOx / NF filter can completely remove the formaldehyde in the glass box within a certain period of time before and after the electrochemical treatment, but the time used is different, 3.5h before pretreatment and 1.1h after pretreatment. The formaldehyde removal rate of the MnOx / NF filter before electrochemical pretreatment was 30% at 30 minutes, while the formaldehyde removal rate of the MnOx / NF filter after electrochemical pretreatment was 85.45% at 30 minutes. Figure 7 As shown, by comparison, it can be seen that the catalytic activity of MnOx / NF filter can be significantly improved by electrochemical pretreatment.

[0064] Example 2

[0065] A plurality of regenerable room temperature catalytic degradation formaldehyde filters were prepared by the method of Example 1 and used in the following room temperature catalytic degradation formaldehyde filter regeneration experiment:

[0066] A room temperature static test was used to simulate the use of the filter: a renewable room temperature catalytic formaldehyde degradation filter prepared as above was taken, sealed with plastic wrap and placed in a 216-liter sealed glass box, and a fixed formaldehyde detector was used to detect the formaldehyde concentration in the glass box in real time. A hose with 1 mL of a certain amount of formaldehyde solution (36-38%) and a fan were also placed in the glass box. The fan was used to evenly disperse the formaldehyde. After the formaldehyde concentration was controlled to be stable at about 1 ppm, the hose was taken out, and then the plastic wrap wrapped around the filter was opened to start the test and record the formaldehyde concentration in real time. A static test was performed after all the formaldehyde in the glass box was removed.

[0067] The filter that has completed a static test is regenerated. The specific regeneration method is as follows: the filter is used as an electrochemical anode, a graphite rod is used as a cathode, and Ag / AgCl is used as a reference electrode to form a three-electrode system. Potassium hydroxide solution (1 mol / L) is used as the electrolyte. The voltage is set to 0.5 V in the electrochemical workstation, and the treatment time is 1 h. After the electrochemical treatment is completed, the filter is heat treated at 70°C in an air atmosphere for 24 h to obtain the regenerated filter.

[0068] The above static test was repeated on the regenerated filter screen obtained in this embodiment, and the above regeneration method was repeated again and a static test was performed after each regeneration. A total of 4 regeneration processes were performed. The half-hour degradation rate obtained in each static test was compared. Figure 8 As shown, it can be seen that the regeneration method of this embodiment can maintain the catalytic activity of the filter at a high level, and the degradation rate of formaldehyde in half an hour is greater than 80%.

[0069] For comparison, a renewable room temperature catalytic formaldehyde degradation filter prepared as above was first subjected to a static test using the above method, and then allowed to stand at room temperature for 24 hours. A static test was performed after each 24 hours of standing at room temperature. After four room temperature standing treatments, the half-hour degradation rate comparison of each static test was as follows: Fig. 9 As shown in the figure, the catalytic performance of the filter has dropped significantly, and the formaldehyde removal rate has dropped rapidly from 82.99% in half an hour to 16.08% in half an hour. Then the filter was regenerated using the above regeneration method, and the half-hour degradation rate of the regenerated filter was tested, reaching 92.33%. The comparison chart with the degradation rate before regeneration is shown in the figure Fig.10The voltage was adjusted to 0.1V or 0.3V during the regeneration process, and it was found that the regeneration effect was poor and the catalytic efficiency of the filter after regeneration was not high. The voltage was adjusted to 0.5V during the regeneration process, and the electrochemical treatment time was 0.25h, 0.5h, 1h and 3.5h. It was found that the catalytic performance of the filter was the best when the electrochemical treatment was 1h.

[0070] Take a renewable room temperature catalytic degradation formaldehyde filter prepared as above and first perform a static test using the above method, then heat treat it at 70°C for 24h in air atmosphere, and perform a static test after each heat treatment at 70°C for 24h. After 4 heat treatments, the half-hour degradation rate comparison of each static test is as follows: Fig.11 As shown, after five static tests, the catalytic performance gradually decreased from 88.46% formaldehyde removal rate in half an hour to 57.14% in half an hour, and the performance decline trend was obvious.

[0071] like Fig.12 For the above MnO x The XPS spectra of Mn 2p on the NF filter before static testing, after five static tests, and after one regeneration treatment show that after five static tests, the Mn 4+ The content is significantly reduced, that is, the average oxidation state of the catalyst is reduced. After one regeneration, the Mn 4+ The content is higher than before static test.

[0072] like Fig.13 For the above MnO x XPS spectra of O1S before static test, after five static tests and after one regeneration treatment of the NF filter. The peak near 532.45 eV mainly includes water and carbonate, which is recorded as O w The peak near 531.05 eV mainly includes surface adsorbed oxygen, formaldehyde and formic acid, which are recorded as O A The peak around 529.55 eV is mainly attributed to the surface lattice oxygen (O latt ). Surface adsorbed oxygen and surface lattice oxygen are generally considered to be surface active oxygen that adsorbs and degrades formaldehyde. Carbonates and formate are intermediates for the conversion of formaldehyde into CO2 and H20. As shown in the figure, after five static tests, the lattice oxygen content on the filter surface decreased significantly, which is related to the reduction of Mn. w and O A The contents of Fig.14 The results of C 1S are consistent.

[0073] like Fig.14 For the above MnO xXPS spectra of C1S of the NF filter before static test, after five static tests and after one regeneration treatment. After the static test, an additional peak appeared near 290eV, which was obviously caused by the accumulation of intermediates. After the regeneration treatment, combined with Fig.11 , 12 and 13, the Mn 4+ The content was restored, and after electrochemical regeneration, O w and O A The content of was lower than that after the static test, and the extra peak in the C 1S spectrum disappeared, indicating that the accumulated intermediates were significantly removed, and the surface lattice oxygen content was restored after regeneration. It is speculated that the electrochemical regeneration restores the catalyst activity by increasing the oxidation state, restoring the surface active oxygen content and removing the accumulated intermediates.

[0074] For those skilled in the art, various corresponding changes and modifications can be made according to the above technical solutions and concepts, and all of these changes and modifications should be included in the protection scope of the claims of the present invention.

Claims

1. A renewable room temperature catalytic degradation formaldehyde filter, characterized in that: The regenerable room temperature catalytic formaldehyde degradation filter is composed of a layer of nano-MnO2 loaded on the surface of nickel foam. x The MnO particles are densely packed x The nano-MnO x The particle size is uniform and evenly distributed on the surface of nickel foam. x The particle size is less than 50nm.

2. The renewable room temperature catalytic degradation formaldehyde filter according to claim 1, characterized in that: The pore size of the nickel foam is in the range of 75-110 PPI; the regenerable room temperature catalytic degradation of MnO on the formaldehyde filter x The loading rate is 5-10wt%.

3. A method for preparing a renewable room temperature catalytic formaldehyde degradation filter according to claim 1 or 2, characterized in that: The specific steps are as follows: S1: prepare sodium thiosulfate aqueous solution and potassium manganate aqueous solution respectively; S2: After cleaning the nickel foam, place it in the sodium thiosulfate aqueous solution and potassium permanganate aqueous solution obtained in step S1 in turn to soak, and generate MnO on the surface of the nickel foam. x , and then dried to obtain MnO x / NF filter; S3: Using a three-electrode method, potassium hydroxide solution is used as the electrolyte, and the MnO obtained in step S2 is used x / NF filter is used as anode, stone mill rod is used as cathode, Ag / AgCl is used as reference electrode, electrochemical reaction is carried out, and finally drying is performed to obtain a renewable room temperature catalytic degradation formaldehyde filter.

4. The method for preparing a renewable room temperature catalytic formaldehyde degradation filter according to claim 3, characterized in that: The concentration of the potassium permanganate aqueous solution in step S1 is 3-5 g / L, and the concentration of the sodium thiosulfate aqueous solution is 10-15 g / L.

5. The method for preparing a renewable room temperature catalytic formaldehyde degradation filter according to claim 3, characterized in that: Step S2 generates MnO on the surface of nickel foam x The method is as follows: the cleaned nickel foam is first immersed in a sodium thiosulfate aqueous solution for 5-10 minutes, and then immersed in a potassium permanganate aqueous solution for 5-10 minutes, which is regarded as one process, and the process is repeated 5-10 times.

6. The method for preparing a renewable room temperature catalytic formaldehyde degradation filter according to claim 3, characterized in that: The concentration of the potassium hydroxide solution in step S3 is 0.5-1.2 mol / L; the electrochemical reaction conditions in step S3 are: reaction voltage is 0.1-0.7 V, and reaction time is 0.5-3.5 h.

7. An air purifier prepared by the renewable room temperature catalytic degradation of formaldehyde filter according to claim 1 or 2.

8. A method for regenerating a regenerable room temperature catalytic degradation formaldehyde filter as claimed in claim 1 or 2, characterized in that: The specific steps are as follows: a three-electrode method is adopted, with potassium hydroxide solution as the electrolyte, a used room temperature catalytic degradation formaldehyde filter as the anode, a stone mill rod as the cathode, and Ag / AgCl as the reference electrode, to carry out an electrochemical reaction, and finally a renewable room temperature catalytic degradation formaldehyde filter is obtained by heat treatment.

9. The method for regenerating a regenerable room temperature catalytic formaldehyde degradation filter according to claim 8, characterized in that: The concentration of the potassium hydroxide solution is 0.5-1.2 mol / L; the electrochemical reaction conditions are: the reaction voltage is 0.1-0.7 V, and the reaction time is 0.5-3.5 h.

10. The method for regenerating a regenerable room temperature catalytic formaldehyde degradation filter according to claim 8, characterized in that: The heat treatment temperature is 50-100°C, and the heat treatment time is 6-24h.